2016
DOI: 10.1038/srep28698
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin induces anti-viral effects in cultured bronchial epithelial cells from COPD patients

Abstract: Rhinovirus infection is a major cause of chronic obstructive pulmonary disease (COPD) exacerbations and may contribute to the development into severe stages of COPD. The macrolide antibiotic azithromycin may exert anti-viral actions and has been reported to reduce exacerbations in COPD. However, little is known about its anti-viral actions on bronchial epithelial cells at clinically relevant concentrations. Primary bronchial epithelial cells from COPD donors and healthy individuals were treated continuously wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 37 publications
5
70
1
2
Order By: Relevance
“…production of sentinel inflammatory cytokines including IL-6, IL-8 and RANTES. Although the antiviral activity of azithromycin has been suggested to occur via its activation of the interferon-beta (IFN-β) pathway, 29,30 the fact that it had no effect on apoptosis in this study, a process typically induced by IFN-β, suggests an alternative mode of action, possibly via lung microbiome modification. 31 Our results appear consistent with that of others, who have demonstrated its antiviral and antiinflammatory nature [26][27][28] suggesting that prophylactic azithromycin may aid in protecting the lungs against viral infection and the resultant inflammatoryassociated damage.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…production of sentinel inflammatory cytokines including IL-6, IL-8 and RANTES. Although the antiviral activity of azithromycin has been suggested to occur via its activation of the interferon-beta (IFN-β) pathway, 29,30 the fact that it had no effect on apoptosis in this study, a process typically induced by IFN-β, suggests an alternative mode of action, possibly via lung microbiome modification. 31 Our results appear consistent with that of others, who have demonstrated its antiviral and antiinflammatory nature [26][27][28] suggesting that prophylactic azithromycin may aid in protecting the lungs against viral infection and the resultant inflammatoryassociated damage.…”
Section: Discussionmentioning
confidence: 55%
“…Although recognized as a common cause of exacerbation and resultant damage in immunocompromised individuals, RV is not the only viral risk factor in allograft recipients. Work by others have identified respiratory syncytial virus (RSV) and influenza as prominent viral pathogens 24,29,30,32 in allograft recipients and hence further research is necessary in order to gain a better understanding of the effects of these respiratory viruses in the lower airways of lung allograft recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Others report that azithromycin primes the host immune response to better resist viral infection . If true, then this mechanism may help to explain how chronic macrolide therapy reduces the risk of or improves recovery from acute pulmonary exacerbations for people with a variety of lung diseases, ranging from CF with or without P aeruginosa infection to COPD in older populations and bronchiolitis in young children . Most recently, azithromycin reduced the time to next exacerbation in young children with CF who developed newly identified P aeruginosa in respiratory cultures.…”
Section: Cellular Contributions To the Cf Airway Inflammatory Responsementioning
confidence: 99%
“…Early in vivo evidence suggested that azithromycin has anti-inflammatory and antiviral effects through induction of interferon-stimulated gene mRNA expression and reduced viral replication and release in patients with asthma and chronic obstructive lung disease. 36,37 In a randomized clinical trial including wheezing preschool-aged children, early azithromycin administration significantly reduced the likelihood of a severe lower respiratory tract infection. 38 Novel macrolides (Mycobacterium avium complex 5) with anti-inflammatory, antibacterial, and, more importantly, interferon-augmenting activity in airway epithelium have been identified.…”
Section: Immune and Antiviral Pathway Modulatorsmentioning
confidence: 99%